Inside China's automobile factories : the politics of labor and worker resistance - Zhang, Lu (Cambridge : Cambridge University Press, 2015)
In Inside China's Automobile Factories, Lu Zhang explores the current conditions, subjectivity, and collective actions of autoworkers in the world's largest and fastest-growing automobile manufacturing nation. Based on years of fieldwork and extensive interviews conducted at seven large auto factories in various regions of China, Zhang provides an inside look at the daily factory life of autoworkers and a deeper understanding of the roots of rising labor unrest in the auto industry. Combining original empirical data and sophisticated analysis that moves from the shop floor to national political economy and global industry dynamics, the book develops a multilayered framework for understanding how labor relations in the auto industry and broader social economy can be expected to develop in China in the coming decades.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Automobile industry workers -- China; Automobile industry and trade -- China; Automobile factories -- China; Industrial relations -- China